ANALYSIS TOWARDS THE IMPACT OF EATR ON FOREIGN INVESTMENT - Arissawarasty Ratih Permataningtyas; Benedictus Raksaka Mahi (EKUITAS (Jurnal Ekonomi dan Keuangan), 2022)
Foreign investment has important role for economic development of a country due to its capabilities to support the acceleration of economic growth in the country as an investment destination. According to these statements, many countries are competing to get foreign investment by setting various investment incentives, one of that is through tax incentives in the form of low tax rates. Therefore this research was conducted with aims to analyze further in how the impact of tax incentives towards foreign investment. In assessing the effectiveness of these tax incentives, it is usually done by low value of Statutory Tax Rates. However, this research indicates that the proper measure to use by Effective Average Tax Rates (EATR) because EATR is considered effective in describing the impact of tax incentives received by investors. This research used panel data from 70 countries from 2017 to 2020. Then these data was processed through OLS, Fixed Effect and Generalized Method of Moment (GMM) methods. From these results it can be concluded that Effective Average Tax Rates have negative and significant impact on foreign investment. The higher the value of Effective Average Tax Rates in a country, the smaller the foreign investment will entering the country.